Prūsų onimų germanizavimo tyrimai K. O. Falko rankraščiuose - Sinkevičiūtė, Daiva; Stundžia, Bonifacas (Baltistica, 2001)
INVESTIGATION INTO THE GERMANIZATION OF OLD PRUSSIAN PROPER NAMES IN THE MANUSCRIPTS OF K. O. FALKTo judge from the manuscripts, one would conclude that K. O. Falk spent a lot of time on the analysis of the Germanization of OPr proper names based on the principles which he had elaborated in the publications on the Slavicization of Lithuanian names. Falk’s main idea is that substitutional and additional final -e is a marker of the weak declension of Middle Low German by means of which the OPr proper names (and sometimes apellatives) were integrated into the morphological system of MLG. The present article includes a list of 31 OPr names with K. O. Fal’'s grammatical and etymological comments.